The Use Of Demonstration Method In Magnetic Media To Improve Students Activity At The Fifth Grade Student In Sd Negeri 08 Pinang Sebatang Timur In Kecamatan Tualang Kabupaten Siak - Mahyar Mahyar (Fakultas Sastra Universitas Ekasakti, 2018)
Students are accustomed to memorizing facts, principles, formulas, laws and problems given by the teacher, thus understanding the concept tends to be low. Description of daily test value obtained from 25 students that is, the average value of 54.80 with the percentage of the value reached 48% only KKM. From the description above we need the new treatments to improve student achievement and learning activities. In order to improve learning outcomes, it can be improved through demonstration methods and media in the form of real objects that exist around, so that students no longer have difficulty in understanding the material. Based on the above, then that becomes the problem in this study can be formulated as follows: 1) Do the media magnets, magnetic objects, cable and battery can improve student achievement at the fifth grade student in SD Negeri 08 Pinang sebatang Timur Kecamatan Tualang Kabupaten Siak about making magnets ? 2) Does the demonstration method can improve students' learning activities at the fifth grade students in SD Negeri 08 Pinang sebatang Timur Kecamatan Tualang Kabupaten Siak about making a magnet? The subject in this classroom action research is a fifth grade students of SDN 08 Pinang sebatang Timur Kecamatan Tualang Kabupaten Siak at the second semester in the academic year 2014/2015 the number of students 25 people, consisting of 9 men and 16 women with different levels of ability to understand the lesson. Classroom action research was carried out in SDN 08 Pinang sebatang Timur Kecamatan Tualang Kabupaten Siak. Researchers take this location or place with the consideration of working at the school concerned, making it easier in search of data, the opportunity of time wide and subject of the research that is in accordance with the profession researchers. Based on the results above we concluded that the application of methods of demonstration can improve student learning outcomes in science subjects in SDN 08 Pinang sebatang Timur Kecamatan Tualang Kabupaten Siak in second semester of 2014/2015.